2022
DOI: 10.5334/aogh.3714
|View full text |Cite
|
Sign up to set email alerts
|

What Do Global Health Practitioners Think about Decolonizing Global Health?

Abstract: The growing awareness of colonialism's role in global health partnerships between HICs and LMICs and the associated calls for decolonization in global health has led to discussion for a paradigm shift that would lead to new ways of engagement and partnerships, as well as an acknowledgement that colonialism, racism, sexism, and capitalism contribute to inequity. While there is general agreement among those involved in global health partnerships that the current system needs to be made more equitable, suggestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…However, our analysis was limited by our small sample size (more than half of the cells had an n < 5), which was not sufficient to produce reliable estimates on the basis of gender (See Supplemental Materials Table S3). [17,18], and decolonizing global health is at present a contested concept [14]. Our respondents' definitions of the concept and their attitudes toward it reflect the significant differences present in the literature around decolonizing global health.…”
Section: Perceptions Of the Impact Of Colonialism On Global Healthmentioning
confidence: 78%
See 1 more Smart Citation
“…However, our analysis was limited by our small sample size (more than half of the cells had an n < 5), which was not sufficient to produce reliable estimates on the basis of gender (See Supplemental Materials Table S3). [17,18], and decolonizing global health is at present a contested concept [14]. Our respondents' definitions of the concept and their attitudes toward it reflect the significant differences present in the literature around decolonizing global health.…”
Section: Perceptions Of the Impact Of Colonialism On Global Healthmentioning
confidence: 78%
“…First, our findings suggest the need for the global health community to develop clarity around exactly what decolonizing global health means. Recent studies involving global health leaders have revealed both agreement and disagreement about the precise meaning of decolonizing global health [ 17 18 ], and decolonizing global health is at present a contested concept [ 14 ]. Our respondents’ definitions of the concept and their attitudes toward it reflect the significant differences present in the literature around decolonizing global health.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the movement to decolonize global health may have developed into an echo chamber of rhetoric, roadmaps, and buzzwords that upholds the very power dynamics it claims to dismantle (Khan et al, 2021). This explains why there is so much contention within the movement about what decolonization ought to look like (Chaudhuri et al, 2021;Mogaka et al, 2021;Finkel et al, 2022). Moreover, this is why we ought to take a step back and a closer look at the reality of the work as it exists today.…”
Section: Introductionmentioning
confidence: 99%
“…Originating in tropical medicine and later in international health, it has colonial baggage that needs to be acknowledged and dealt with. Calls for ‘decolonising global health’ have been voiced 2. At the same time, old structures prevail and are reproduced 2.…”
mentioning
confidence: 99%
“…Calls for ‘decolonising global health’ have been voiced 2. At the same time, old structures prevail and are reproduced 2. This is troublesome since the colonial narrative lingers on and thereby hampers the potential for global health to contribute to addressing the challenges it is fit for.…”
mentioning
confidence: 99%